P. КULISH AND EUROPEAN LITERATURE: CRITICAL RECEPTION OF THE INTERWAR DECADES - Devdiuk, Ivanna; Marchuk, Tetiana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
Aim. The article is devoted to the analysis of P. Kulish’s research discourse of the first decades of the twentieth century. Its aim is to comprehend the literary-critical studies of the interwar period, focusing on the peculiarities of Kulish’s interpretation of European artistic experience. Methods. The theoretical and methodological basis of the paper is the receptive-communicative approach, which made it possible to consider the critical reception of P. Kulish’s work as a communicative process between the author and addressees, whose individual consciousness was formed in certain socio-political and cultural-historical environments. Results. In the course of the study, it has been proven that the question of P. Kulish’s Europeism was at the centre of intellectual discussions of the day concerning the ways of Ukrainian literature further development. Having become the key point in the choice between the past and the future, traditional and innovative, its own and others, it directly affected the authenticity of the national life of the Ukrainians. In the studies of M. Zerov, M. Mohylianskyi, B. Neiman, V. Petrov, P. Fylypovych, M. Khvylovyi, and others, the foundations were laid for a critical comprehension of Kulish’s heritage, who appealed for thoughtful mastering of foreign-language cultural experience as an important component of national progress. The high professionalism demonstrated in the research laid the groundwork for modern Kulish studies, which exemplify a communicative polylogue open to further scientific search. Originality. The research summarises the factors that writers and critics turn to the figure of P. Kulish; the kinship of the ideological and artistic searches of the figures of the time with the cultural visions of the author of “Black Council” has been traced; and the place and role of the research in the spiritual and cultural progress of the age have been defined. Practical significance. The results of this article can be used in the course of studying P. Kulish’s work in general, as well as in the aspect of communicative connections between Ukrainian and foreign literature.